Impact of Dynamic LED Non-Linearity on DCO-OFDM Optical Wireless Communication - Linnartz, Jean-Paul M. G.; Deng, Xiong; Van Voorthuisen, Paul (IEEE communications letters, 2021)
DC-Offset Orthogonal Frequency Division Multiplexing (DCO-OFDM) is a popular modulation method for Optical Wireless Communication (OWC) as it can assign specific power levels and constellations to different subcarrier frequencies across the low-pass response of the LED. However, LEDs exhibit dynamic non-linearities to which OFDM is very sensitive. As LED signals are subject to non-linear memory effects in photon generation, different OFDM subcarriers experience different amounts of distortion. This letter translates the LED behavior into a communication channel model for OFDM modulation. It gives an experimentally verified expression for the Signal-to-Distortion Ratio (SDR) as it varies per subcarrier in OFDM systems.